First-year seminar intervention: Enhancing firstyear mathematics performance at the University of Johannesburg (Journal of Student Affairs in Africa, 2021)
South Africa has opened up access to higher education over the past 20 years. The massive increase in enrolments (with almost 70% first-generation students) substantially affects progress and graduation rates in Science programmes in higher education. First-year students in Science realise that universitymathematics requires knowledge and skills that are not part of their academic repertoires. Science students at the University of Johannesburg register for a two-week, credit-bearing First-year Seminar (FYS). The research question that this paper addresses is: What is the relationship between the Firstyear Seminar and the mathematics performance of first-year students in Science? The specific purpose is to determine the relationship between: (1) students’ school mathematics background; (2) the problemsolving skills sessions of the FYS; and (3) their first-year performance in mathematics. It was foundthat the FYS  enhances students’ ability to make a successful transition to university, with problemsolving ability acting as a fair predictor of performance in first-year mathematics. The empirical data was collected through a before-and-after test performed by the 2014 cohort with regards to students’attendance of the FYS. Notably, the data indicate that the value added by the problem-solving test can be applied to identify and engage students who have high probability of becoming students at risk (STARs).
Keywords: Higher education; teaching and learning; first-year student experience; mathematics performance; University of Johannesburg; South Africa